Enterprise Architecture Design Using TOGAF ADM for Digital Transformation at PT Profito Inovasi Kreatif - Allegra Aretha Putri; Nadine Aurelia; Vera Veronika; Fransiska Eka Putri Wiriady; Afifah Trista Ayunda (ULTIMA InfoSys, 2026)
The rapid development of information technology encourages companies to adopt digital transformation to improve operational efficiency and business competitiveness. PT Profito Inovasi Kreatif, a distribution company, has implemented information systems such as ERP, CRM, and cloud-based services to support its operations. However, the company still faces several challenges, including declining ERP performance due to increasing data volume, complex data management with more than 6,000 SKUs, and inefficient distribution processes. This study aims to design an Enterprise Architecture using the TOGAF ADM framework. A qualitative case study approach was employed, with data collected through interviews and analysis of operational activities. The analysis identifies current (as-is) and proposed (to-be) conditions across business, application, and technology architectures. The results propose the development of an internal ERP system, implementation of a Transportation Management System (TMS) for automated route planning, and enhanced system integration. These solutions are expected to improve operational efficiency, optimize data management, and support real-time decision-making in the organization.